Investigation of binaural beats and isochronic tones on beta and gamma brain wave frequencies / Syarifah Noor Deraman@Abd Rahman - Deraman@Abd Rahman, Syarifah Noor (2015)
Electrical impulses and chemical activities in human brain generate brain waves at distinct frequency domains between 0.5 and 100 Hz. These domains are associated with different brain activities and are characteristic of different mental states. The cerebral brain cells, which produce the frequency patterns in accordance to the brain activity, can be synchronized to a desired frequency by externally stimulating the cells using acoustical means including binaural beats (BB) and isochronic tones (IT). This thesis presents the preliminary investigation of the effectiveness of IT over BB on stimulating the mental states of alertness and attention on human brain at the Beta (20 Hz) and Gamma (40 Hz) domains. Electroencephalograph (EEG) potentials are measured on 50 healthy male subjects based on the International 10/20 System of Electrode Placement. The results indicate that both pure and embedded IT have an improved effect over BB on the EEG potentials measured at the pre-frontal cortex (PFC) locations by 17% and 36%, respectively, and render a positive influence on the focus and attention mental states of the brain. It also indicates that the embedded signals has an effect comparable to pure signals on the EEG potentials measured at the PFC locations. BB and IT signals embedded in a background audio can provide better listening comfort. The effects of peri-synchronization of pure IT are also investigated and found that the EEG potentials at the anterior frontal region increased by 11.4% and 72.3% from the baseline values at the Beta and Gamma rhythms, respectively.